Gambaran Status Gizi Dan Perilaku Konsumsi Minuman Manis Siswa MI Di Pondok Tahfidz Saffiyan Hafiyya Ogan Ilir - Supriyati, Dina (Universitas Ivet, 2025)
Diabetes mellitus is one of the chronic diseases that is no longer limited to the adult age group but is also increasingly found in the child population. Modern lifestyle changes, especially the consumption patterns of high-sugar but low-nutrient beverages, have become the main factor contributing to the rise of diabetes mellitus cases at an early age. Data from the Indonesian Pediatrician Association (IDAI) shows that as many as 1,645 children in Indonesia have been diagnosed with diabetes, spread across 13 major cities. This study aims to explore the consumption habits of sweet beverages and assess the nutritional status of students at MI Pondok Saffiyan Haffiya. The research approach used is descriptive quantitative with a cross-sectional design and total sampling technique. The findings show that as many as 3 students (5%) are in the overweight category. The consumption habits of sweet drinks in the last week include: boxed milk consumed by 26 students (74.3%), soft drinks like Coca-Cola or Sprite by 8 students (22.9%), sweet tea by 15 students (42.9%), ice cream by 16 students (45.7%), and boba drinks by 10 students (28.6%). Obesity in children is generally caused by an imbalance between energy intake and expenditure, especially due to the consumption of high-sugar drinks without sufficient physical activity. Therefore, interventions through nutrition education and the promotion of healthy lifestyles from an early age are crucial strategies in efforts to prevent diabetes mellitus in children.